Banking financial performance during Covid-19 - Wardhani, Rulyanti Susi; Rosalina, Erita; Elvany, Ratih; Awaluddin, Murtiadi (Technium Social Sciences Journal, 2021)
Pandemic Covid-19 has made every company improve its business operations, continue to run well, and produce good financial performance optimal. Financial performance is a measuring tool for describing the financial conditions of a company. Measurement of financial performance in this study using the DuPont system method. The reason for this consideration is to analyze contrasts in money related execution sometime recently and amid Covid-19 and analyzing the impact of the pointers contained on Dupont framework strategies, to be specific Net Benefit Edge (NPM), Total Asset Turnover (TATO), Financial Leverage Multiplier (FLM), Return on assets (ROA) and Return On Equity (ROE). This study’s population is a listed banking sector company Indonesia Stock Exchange (IDX), for the period 2019-2020. This study’s sample is based on a purposive sampling technique to obtain as many as 23 banking companies. Information in this think about was analyzed by Wilcoxon signed-rank test approach. The test result shows that the sector’s financial performance banking experienced no difference before and during Covid-19. This research strengthens the implementation of government policies as outlined in OJK Regulation Number 11/POJK.3/2020 concerning relaxation of credit restructuring. Thus, banks are still able to maintain banking financial stability during a pandemic. Keywords: Covid-19, Financial Performance, Banking